Reactions of 4-Benzoyl-1,5-diphenyl-1H-pyrazole- 3-carboxylic Acid with Hydrazides - UNAL, DILEK; ALTURAL, BEHZAT (Asian Journal of Chemistry, 2010)
The reaction of substituted pyrazole ring 3 with various hydrazides (4a-f) furnished the corresponding pyrazole carbohydrazides (5a-f). The structures of the novel compounds were confirmed by elemental analysis, IR, 1H and 13C NMR spectroscopic measurements.